HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP IBU HAMIL RESIKO TINGGI AKIBAT PERNIKAHAN USIA MUDA DI WILAYAH KERJA PUSKESMAS CELALA KABUPATEN ACEH TENGAH - Nurlaely HS; Mawadhah Yusran Yusran (Universitas Prima Indonesia, 2023)
ABSTRACT Detection of risk factors 7 for pregnant women can be done by the community in an effort to prevent maternal and infant deaths. As soon as a child has a planner, he must prepare everything from the outward, inner, and economic. Preliminary studies conducted in January at the Celala Health Center in December 2018 with 680 pregnant women in one year and 200 high-risk pregnant women (30.1%). The purpose of this study is to find out the relationship between the level of knowledge of young pregnant women with high risk pregnancy (Resti) in the work area of the Celala Health Center, Celala District, Central Aceh Regency in 2019. This research method is descriptive analytic with cross sectional design. Total population of 200 respondents with a total sample of 67 respondents. This research was conducted in the Work Area of the Celala Health Center on 17 to 21 Maret 2023. The results of statistical analysis using the Chi Sqare test obtained the value of P value = 0.003 <0.05 this case shows that there is a relationship between the level of knowledge of pregnant women at high risk due to young marriage, P value = 0.004 <0.05. This indicates that there is a relationship between the knowledge level of pregnant women at high risk due to young marriage. During pregnancy it is advisable for pregnant women not to do physical labor that is too heavy, but it is advisable to do a lot of pregnancy exercises to expedite the delivery process later. Keywords: Knowledge, Attitudes of Young Pregnant Women, High Risk